Legal Experts' Perceptions Regarding the Dissenting Opinion of Constitutional Court Judges (Study: Constitutional Court Decision Number 90/PUU/XXI/2024) - Kadir, Syukron Abdul; Subaidi, Subaidi; Pratita, Afifah Rahma; Mahditya, Alma; Ningrum, Anna Cahya; Herawati, Alifah; Ferdiyansyah, Imam Denis; Sulhan, Sulhan; Wibowo, Ari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The text discusses the dissenting opinion in the decision of the Constitutional Court Judge in the case of the petition a qua No. 90/PUU-XXI/2023 which examines article 169 letter q regarding the minimum age limit requirements for presidential and/or vice-presidential candidates. The dissenting opinion in the decision has generated both pro and contra perceptions from legal experts. However, the dissenting opinion of some Constitutional Court Judges does not invalidate the decision; the decision is final and can be enforced as determined by the Constitutional Court. Methodologically, this research uses a normative research method through library research, which includes legal materials related to the formulation of the problem, such as legislation, books, journals, and other related readings. These materials are then systematically collected, organized, and examined in order to draw a conclusion to address the problem formulation.